The use of cyclic voltammetry to detect biofilms formed by Pseudomonas fluorescens on platinum electrodes - Vieira, M. J. (2003)
The development of an electrochemical detector to monitor the in situ formation of biofilms is described. The detector consisted of an electrochemical cell containing three electrodes, whose response to the application of a potential profile to the working electrode was sensitive to the amount of biofilm present on the surface. The electrochemical technique used was repetitive cyclic voltammetry. Differences between the response of the uncolonised electrode and after Pseudomonas fluorescens biofilms of different ages were grown on its surface were determined. The results show that cyclic voltammetry applied to platinum electrodes can be used to detect young biofilms. The development of the shape of the voltammogram as the potential is cycled may constitute a means of providing information on the coverage of the surface. Observation of the platinum electrodes before and after the electrochemical measurements showed that even after 30 min of recycling, most of the cells were still adhered to the surface, although some may have lost viability.